2019
DOI: 10.1159/000505833
|View full text |Cite
|
Sign up to set email alerts
|

Muslims’ Affective and Cognitive Attitudes towards Formal Dementia Care in South Africa: Do They Vary according to Family Structure and the Experience of Familial Caregiving?

Abstract: Background: The feelings and beliefs of some social groups sharing the same values about formal care institutions impacts their likelihood of using such services. Socialisation theory posits that there should not be any difference in attitudes towards formal care in the Muslim community, as they are influenced by the principles of Confucianism. However, demographic, epistemological, and socio-economic trends, as well as globalisation, may be impacting the efficacy of caring for people with dementia (PWD) at ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Negative attitudes to formal care exist among some family members and in some societies irre-spective of economic status, with religious beliefs contributing to the perspective. 131 A study in South Africa showed that less than one third of respondents were willing to pay for formal home caregivers, with higher education, female sex, and older age associated with willingness to pay. 132 The challenges of formal care setting include the risk of delirium associated with dementia due to infective causes.…”
Section: Living With Dementia In Africamentioning
confidence: 99%
See 1 more Smart Citation
“…Negative attitudes to formal care exist among some family members and in some societies irre-spective of economic status, with religious beliefs contributing to the perspective. 131 A study in South Africa showed that less than one third of respondents were willing to pay for formal home caregivers, with higher education, female sex, and older age associated with willingness to pay. 132 The challenges of formal care setting include the risk of delirium associated with dementia due to infective causes.…”
Section: Living With Dementia In Africamentioning
confidence: 99%
“…To relieve caregiver burden, formal home care is a viable option in high‐income countries but not in Africa. Negative attitudes to formal care exist among some family members and in some societies irrespective of economic status, with religious beliefs contributing to the perspective 131 . A study in South Africa showed that less than one third of respondents were willing to pay for formal home caregivers, with higher education, female sex, and older age associated with willingness to pay 132 .…”
Section: Current Evidencementioning
confidence: 99%
“…Only 28% of the respondents in our sample were agreeable to paid home caregiving for PWD. This was not an unexpected result, however, as research has shown how in societies where co-residential setups are preferred, attitudes towards and the use of external services is generally not accepted [3,17,37]. In addition, for Muslim societies, religion has been shown to play a role in slowing cognitive decline, is a coping strategy, and has a positive impact on quality of life for PWD [2,39].…”
Section: Discussionmentioning
confidence: 94%
“…Cultural norms influence the type of care arrangements for the elderly, with familial cultures more likely to show a preference for home-based care [37]. The value of filial piety which underpins Islam influences the negative perceptions towards delegating caregiving outside the family network [2,4,17]. Economic development and globalisation are impacting the family support network globally, however, resulting in an aging population and an increase in the residential separation of generations [2,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation